Quantification of chlorogenic acid, rosmarinic acid, and caffeic acid contents in selected Thai medicinal plants using RP-HPLC-DAD - Chayanon Chaowuttikul; Chanida Palanuvej; Nijsiri Ruangrungsi (Universidade de São Paulo, 2020)
The chlorogenic acid, rosmarinic acid, and caffeic acid contents in 100 selected plants were determined using reversed phase high performance liquid chromatography equipped with diode array detector. The optimum condition was 0.2% phosphoric acid in water (solvent A) and methanol (solvent B) as the mobile phase, which was set at 45% B for 20 minutes at a flow rate of 1.2 mL/min. The column temperature was maintained at 30 ºC and the detection wavelength was 325 nm. Among 100 selected plants, 39.64% contained all 3 compounds, 40.54% contained 2 compounds, 14.41% contained only 1 compound, and 5.41% could not detect any of the 3 compounds. The highest contents of chlorogenic acid, rosmarinic acid, and caffeic acid were found in Lonicera japonica flowering buds, Melissa officinalis leaves, and Coffea canephora seeds at the concentration of 9.900 ± 0.004, 19.908 ± 0.171, and 1.233 ± 0.003 g/100 g of dried plant, respectively.